Preparation of novel curdlan nanoparticles for intracellular siRNA delivery. (6th March 2015) - Han, Jingfen; Cai, Jia; Borjihan, Wuyinga; Ganbold, Tsogzolmaa; Rana, Tariq M.; Baigude, Huricha
Highlights: Water soluble curdlan derivatives were prepared and fully characterized. The intracellular siRNA delivery efficiency depends on content of 6-amine units. 6-Amino curdlan/siRNA forms nanoparticles. 6-Amino curdlan efficiently delivered siRNA to cancer cells and stem cells. We report a novel curdlan-based siRNA delivery system. Abstract: RNA interference (RNAi) down-regulates gene expression post-transcriptionally, which is a therapeutically significant phenomenon that could potentially reduce the level of disease related proteins that are undruggable by conventional small molecular approaches. However, clinical application of small interference RNAs (siRNAs) requires design of potent siRNA sequences and development of safe and efficient delivery systems. To create a biocompatible siRNA delivery agent, we chemically modified natural polysaccharide curdlan in a regioselective manner to introduce amino group in the glucose units. The resulting 6-amino-curdlan (6AC) is water soluble and forms nanoparticles upon complexing with siRNAs. The novel curdlan-based nanoparticles efficiently delivered siRNAs to human cancer cells and mouse primary cells, and reduced 70–90% of target mRNA level. Moreover, 6AC nanoparticles delivered siRNA targeting eGFP to mouse embryonic stem (mES) cells stably expressing eGFP, and produced substantial reductions of GFP protein level. The novel curdlan-based nanoparticle is a promising vehicle for delivery of short RNAs to knock down endogenous mRNAs.